CHANGE IN CONTENT OF GLYCOPROTEINS ON THE SURFACE OF ENDOTHELIAL CELL CULTURE EA.HY 926 AND INTIMA OF INTERNAL CAROTID ARTERIES UNDER THE INFLUENCE OF MAGNESIUM OROTATE - L. V. Didenko; E. A. Ulubieva; T. G. Borovaya; A. G. Avtandilov; N. V. Shevlyagina; V. G. Zhukhovitsky; O. M. Grinkevich; M. V. Mezentseva (Рациональная фармакотерапия в кардиологии, 2017)
Aim. To study changes in the glycoproteins content in the glycocalyx of endothelial cells under the influence of magnesium orotate.Material and methods. Endotheliocytes of cell culture EA.hy 926 were examined before  and after addition of the magnesium orotate to the culture medium. Intimal endothelium of internal carotid arteries, fragments of which were obtained by sequential execution of bilateral resection of the arteries before  and after course of treatment with magnesium orotate was also investigated. Anthony’ method (1931), designed for the study of glycoproteins in the bacteria capsule and adapted by L.V. Didenko (2013) for eukaryotes was used to detect glycoproteins. The scanning electron microscopy with simultaneous x-ray microanalysis was applied.Results. Total number of Cu2+-signals per one scanning field in the mapping of samples for Cu2+ as the indirect index of proteoglycan content in EA.hy 926 endothelial cell culture before incubation with magnesium orotate was 6928±124, and after incubation with magnesium orotate – 7592±131. Number of Cu2+-signals on the surface of the internal carotid artery intima before treatment with magnesium orotate was 5015±407, and after treatment – 6100±152 per one scanning field.Conclusion. A significant increase in the content of glycoproteins on the surface of EA.hy926 endothelial cell culture (+10%) and internal carotid artery intima (+22%) under the influence of magnesium orotate was found.